JSTOR's "Data for Research": A Bibliometric Analysis of Mathematics in Economics. - Art King; Brian Simboli; Kevin Rom (Issues in Science and Technology Librarianship)
The "Data for Research" (DfR) service facilitates bibliometric studies of key terms and phrases that appear in the full text of JSTOR articles. This platform provides faceted searches that supplement JSTOR's standard search engine, exemplifying how a full text data base enables data mining for the average end-user. We provide a comparison with existing full-text databases, illustrate the mathematization of economics, and suggest a few possible future enhancements. [ABSTRACT FROM AUTHOR]